An exploratory study on organisational adjustments due to Green IT. (24th November 2010) - Sayeed, Lutfus; Gill, Sam
The objective of this study is to empirically explore the impact of the implementation of Green IT measures on organisational resources. To this end, this paper integrates two streams of research: (1) the adoption of Green IT measures and (2) the resource-based view of a firm. The findings suggest that organisations had to reconfigure their IT and non-IT resources in order to implement Green IT initiatives. Moreover, two organisations in our sample of ten have been successful in mobilising their resources by offering new products and services as a result of implementing Green IT. The findings also indicate that organisation-wide awareness and support of Green IT are critical to initiating strategic actions in this area.